The problem of sharing a common stock : an analysis of the mackerel conflict in the North East Atlantic - Hotvedt, Bjørnar Dahl (Universitetet i Tromsø, 2011)
This study examines the reasons why the European Union (EU), Norway, Iceland and the Faroe Islands have been unable to reach an agreement for the distribution of the Total Allowable Catch for Atlantic mackerel. Whereas the allocation previously was decided by the long-standing coastal states, the EU, Norway and the Faroe Islands, changes in the mackerel’s migration pattern in a northward direction has led to Icelandic and Faroese requests for a larger portion of the resource. The “mackerel conflict” breaks out in 2010 and entails the use of sanctions as well as the setting of unilateral quotas in addition to those following from the coastal state agreement. The combined quota demands far exceed sustainable harvesting levels and will by all likelihood lead to overexploitation. The research methods were qualitative and involved the application of two-level game theory and the consideration of “win-sets” to explain the absence of co-operative management. The main finding was that the pelagic fishers effectively enjoy veto power over the outcome of the negotiations, in particular in fishery-dependent Iceland and the Faroe Islands, but to a large extent in Norway as well. Also in the EU the affected fishers have a decisive influence, although only in political terms. The parties’ many attempts at influencing each other’s positions have so far had no discernable effects and the situation begins to bear resemblance to a “tragedy of the commons”. Key words: Atlantic mackerel, European Union, Norway, Iceland, Faroe Islands, TAC, quotas, conflict, two-level games, tragedy of the commons.